PHP, mySQL and apache - Meloni, Julie C. (Sams, 2005)
You own your own business. You have also created a website for your business that details the products or services that you offer, but it doesn't allow potential customers to purchase anything online. Don't risk losing business-learn to create a dynamic online environment using only three programs. PHP, MySQL and Apache are three popular open-source tools that can work together to help you create a dynamic website, such as an online shopping experience. Sams Teach Yourself PHP, MySQL and Apache All in One is a complete reference manual for all three development tools. Learn how they work individually and more importantly, how they work together to create your dynamic website. Use the book and the included CD to create a simple website, as well as a mailing list, online address book, shopping cart and storefront. Open your website to limitless possibilities with Sams Teach Yourself PHP, MySQL and Apache All in One.